Para una relectura de la critica a la razón de Theodor W. Adorno y Max Horkheimer - Abril, Francisco (ARFIL y UNL, 2018)
This paper aims to offer an analysis of the critique of reason developed by Max Horkheimer and Theodor W. Adorno in three of his most important books: Dialectic of Enlightenment, The critique of instrumental reason and Minima Moralia. Two fundamental questions are posed: Does the thought of the authors set a radical critique? If this is the case, would’'t it imply a series of meta theorical problems and contradictions? In order to treat these questions, the statement is divided into two parts. The first explores the recurring issues of the critique of reason. In the second, we elaborate a brief reconstruction of two opposite hermeneutics of Horkheimer and Adorno’s works: on the one hand, the lecture of Frankfurt School’s second generation (Jürgen Habermas and Albrecht Wellmer); on the other hand, Juan José Sánchez’s exposition. Our principal contribution to this debate is to warn Sánchez that, in his justified intention of separating from Habermas and postmodern’s reading, he finally weakens the contradictory and negative tone of Adorno and Horkheimer’s philosophy.